A Decade of Research on Speaking for Academic Purposes (2015–2025): Methodological Patterns, Pedagogical Tools, and Emerging Directions - Yugafiati, Rasi; Yuliasri, Issy; Widhiyanto , Widhiyanto (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
Speaking for Academic Purposes (SAP) has become an increasingly important focus in applied linguistics as learners worldwide strive to meet the demands of higher education. However, challenges such as pronunciation problems, limited fluency, grammar and vocabulary errors, anxiety, and restricted opportunities for authentic communication continue to hinder academic oral performance. This study systematically reviews fifty-two peer-reviewed articles published between 2015 and 2025 to map methodological patterns, country-level research distribution, recurring challenges, and implemented strategies in SAP instruction. Guided by the PRISMA framework, the review applied transparent phases of identification, screening, eligibility, and inclusion, resulting in a consolidated body of studies for synthesis. Findings reveal a predominance of mixed-methods and quasi-experimental designs, indicating a trend toward integrating quantitative measurement with qualitative insights. Indonesia and China emerge as leading contributors to the field, while many other regions remain underrepresented. Across contexts, four recurring obstacles are consistently documented: linguistic limitations, particularly pronunciation; psychological barriers such as anxiety and low confidence; pedagogical constraints linked to teacher-centered approaches; and technological challenges including limited access and digital literacy. Diverse strategies have been implemented, ranging from AI-driven feedback and automatic speech recognition to multimodal practices such as dubbing, audiovisual translation, and virtual reality. These approaches enhanced learners’ fluency, accuracy, and motivation, especially when combined with learner-centered pedagogy that promotes autonomy and collaboration. The review concludes that future research should address long-term sustainability, broaden coverage across populations and contexts, and integrate theoretical perspectives such as communicative competence and multiliteracies. These directions will support the development of more inclusive, coherent, and innovative models of academic speaking instruction.